A CASE OF SIMPLE STERCORAL ULCER OF THE TRANSVERSE COLON - HAGA, Shunsuke; OGAWA, Kenji; KAJIWARA, Tetsuro; WATANABE, Toshiaki; UTADA, Yoshihito (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2001)
A 35-year-old man, who had no paticular history except occasional symptoms of troublesome defecation, was sdmitted to the hospital because of sudden onsets of bloody stool. The appetite was fair and bowel movements were good. No tumor was palpable by a digital examination. Colonoscopy revealed a transeverse colon ulcer with bleeding from a visible vessel, and endoscopic clipping was successful. A biopsy specimen showed hemmorrage into the interstitial tissue, and infiltration of inflam-matry cells and granulation tissue were histologically noted. No specific findings suggestive of inflamma-tory bowel disease, nor infectious colitis were demonstrated. Probable causes in this case are thought to be an impact on the faecal materials, troublesome defecation and a mechanical pressure effect on the mucosa. Simple stercoral ulcer of the transverse colon was definitely diagnosed.